Tourism Today: Trends, Challenges, and Opportunities - Sabbir Ahmed (Lembaga Bale Literasi, 2025)
The global tourism industry is undergoing rapid transformation, driven by technological advancements, environmental imperatives, socio-cultural shifts, and the prolonged effects of the COVID-19 pandemic. This study critically examines the current trends shaping tourism, identifies persistent challenges, and explores strategic opportunities for sustainable growth. Utilizing a qualitative research approach grounded in thematic content analysis, the study synthesizes data from peer-reviewed literature, international policy documents, and industry reports published between 2018 and 2024. The findings reveal that digital transformation—through innovations such as mobile applications, artificial intelligence, and smart tourism platforms—has significantly redefined tourist behavior and destination management. Sustainability has emerged as a critical priority for both policymakers and travelers, prompting increased investment in eco-friendly practices and community-based tourism. Additionally, the rise of personalized and experiential travel underscores a shift toward authenticity and cultural engagement. The post-pandemic recovery has accelerated preferences for domestic travel, flexible booking policies, and heightened health and safety protocols. However, challenges such as climate change, workforce shortages, over-tourism, and geopolitical instability continue to hinder the sector's resilience. The study highlights opportunities in technology integration, rural tourism development, public-private collaboration, and education for workforce enhancement. By offering a comprehensive and evidence-based analysis, this article contributes to the academic discourse on tourism and provides actionable insights for stakeholders aiming to navigate the complexities of a rapidly evolving global tourism landscape